INNOVATIVE TECHNOLOGIES IN THE PROCESS OF AVIATION IMPACT ON THE ENVIRONMENT - Чулінда, Людмила; Бем, Наталія (SWorldJournal, 2025)
The article explores the possibilities of innovative technologies in the field of reducing the environmental impact of aviation by 2050 to create a better aviation space for future generations, reducing the global impact on the climate. Member states of i